Effect of the Ultraviolet C Light-Emitting Diode Treatment on the Quality of Soil-Grown and Pot-Grown Red Raspberries - Nicole R. Giuggioli; Daniele M. Nucera; Serenella Piano; Selene Ollani (Polish Journal of Food and Nutrition Sciences)
Red raspberries (Rubus idaeus L.) are often chosen by consumers for their flavour, taste, and health-promoting properties A relevant issue related to these fruits is their high perishability. The aim of this study was to investigate the effect of the ultraviolet C light-emitting diode (UVC-LED) treatment on soil-grown and pot-grown raspberries in extending their shelf-life, maintaining their high quality throughout the preservation period, and improving features related to their phenolic compound content. The UVC-LED treatment increased the total phenolic content (158 to 200 mg GAE/100 g) and ferric reducing antioxidant power (55.3 to 78.6 mmol Fe 2 +/kg) of the pot-grown raspberries when the UVC-LED treatment was followed by storage in a climate-controlled room (20°C). Total anthocyanin content did not increase significantly compared to the control samples. Contrary to expectations, no effect of reducing the microbial count after storage was observed due to the exposure of raspberries to the UVC-LED radiation. The positive outcomes derived from the analyses of bioactive compounds may be implemented in further studies on the same matrix to better manage the treatment and its conditions, such as the exposure time, the distance from the LED lamps, and the UVC-rays’ dose, in order to find the best combination in terms of efficacy and efficiency.